(untitled) - Stein, Gertrude (New York, NY, 1998)
Gertrude Stein achieved fame for her (often) difficult, (frequently) inaccessible prose and her celebrated circle of friends--a group that included Hemingway, Picasso, Matisse, and F. Scott Fitzgerald. She became notorious for her long-time love affair with Alice B. Toklas and for the questions of possible collaboration that were raised in the wake of her surviving the German occupation of Paris during World War II. During the course of her lifetime and in the decades following her death in 1946, her reputation as an artist has been alternately dismissed and rehabilitated; now the Library of America has canonized her in two volumes
Keywords: American literature; 20th century